Protecting Privileged Cloud Accounts in Banking Systems Through Advanced PAM Solutions (Journal of Artificial Intelligence Research, 2022)
The proliferation of cloud computing in the banking sector has introduced both unprecedented opportunities and significant security challenges, particularly concerning the management and protection of privileged cloud accounts. These accounts often hold elevated permissions, rendering them high-value targets for malicious actors. The complexity of cloud environments and the dynamic nature of modern banking systems necessitate robust Privileged Access Management (PAM) solutions tailored to cloud-specific requirements. This paper examines advanced strategies for protecting privileged cloud accounts in banking systems, with a focus on secure credential storage, just-in-time (JIT) access mechanisms, and monitoring administrative actions. Employing technical tools such as CyberArk and AWS Secrets Manager, the study evaluates their efficacy in mitigating risks associated with unauthorized access, insider threats, and privilege escalation attacks.The research first delves into secure credential storage techniques, emphasizing encryption, role-based access controls, and integration with hardware security modules (HSMs). By leveraging CyberArk's Vault technology and AWS Secrets Manager, organizations can centralize sensitive information, enforce strict access policies, and ensure compliance with regulatory frameworks such as GDPR and PCI DSS. Furthermore, the implementation of JIT access mechanisms is explored as a critical measure to minimize the attack surface. This involves granting ephemeral, task-specific permissions to users and applications, thereby reducing the risk of lateral movement within the network. Solutions like CyberArk's Alero and AWS Identity and Access Management (IAM) policies are analyzed for their effectiveness in achieving this objective.The paper also highlights the importance of comprehensive monitoring of administrative actions within cloud environments. Real-time auditing, behavioral analytics, and anomaly detection are essential for identifying suspicious activities and responding promptly to potential breaches. Advanced PAM solutions integrate with Security Information and Event Management (SIEM) systems, enabling a holistic view of privileged access activities. Case studies from leading banking institutions illustrate the practical applications of these technologies, demonstrating how they enhance operational efficiency while maintaining robust security postures.Additionally, the study addresses the challenges of implementing advanced PAM solutions in hybrid and multi-cloud architectures. These include the complexities of interoperability, scalability, and maintaining consistent security policies across diverse platforms. Recommendations are provided for adopting a layered security approach that combines PAM tools with complementary measures such as zero-trust architectures, endpoint protection, and continuous compliance monitoring.This research underscores the critical role of advanced PAM solutions in safeguarding privileged cloud accounts in banking systems. As the industry continues to embrace cloud technologies, a proactive and adaptive approach to privileged access management is imperative to counter evolving cyber threats. Future directions for research include exploring the integration of PAM solutions with artificial intelligence (AI) and machine learning (ML) to enable predictive threat detection and automated remediation.
Keywords: privileged access management; secure credential storage